Private information in executives' option trades: Evidence from the UK - Kyriacos Kyriacou; Kul B. Luintel; Bryan Mase (Cardiff University, Cardiff Business School, 2008)
UK executives' stock option exercises and associated sell decisions are motivated by private, inside, information. Executives use their inside information to lock in short-term gains, and to sell stock acquired prior to negative abnormal stock returns. This informed trading is robust to the alternative factors that might motivate the exercise of executive stock options, including option moneyness and value of exercise. We suggest that the disparity in informed trading between US and UK executives' option trades is related to important differences in the proportion of executive remuneration linked to options, the regulation of options, and the taxation of option gains. Copyright (c) The London School of Economics and Political Science 2009.
Keywords: 330; Führungskräfte; Aktienoption; Optionsgeschäft; Asymmetrische Information; Großbritannien